Stress hyperglycemia ratio is a risk factor for mortality in trauma and surgical intensive care patients: a retrospective cohort study from the MIMIC-IV - Yingying Zhang; Yu Yan; Lele Sun; Yibo Wang (European Journal of Medical Research)
Abstract Background Stress hyperglycemia ratio (SHR) can reduce the impact of baseline glucose on the stress hyperglycemia level. Studies have shown that SHR is associated with adverse outcomes. However, its relationship with the prognosis of trauma/surgical ICU patients has not been fully studied. The objective of this study was to explore the relationship between SHR and the short-term and long-term mortality in trauma/surgical ICU patients. Methods Clinical data of trauma/surgical ICU patients were extracted from MIMIC-IV. The primary outcome was 28-day all-cause mortality, and the secondary outcome was 365-day all-cause mortality. Boruta algorithm was used to screen the important features related to the 28-day mortality, and Kaplan–Meier curve, Cox proportional hazards regression, and restricted cubic spline were used to explore the relationship between SHR and clinical outcomes. Results A total of 1744 patients were included, of whom 786 were male and 958 were female. The 28-day and 365-day mortality rates were 14.7% and 27.2%, respectively. Multivariate Cox proportional hazards analysis showed that an increase in SHR was significantly associated with an increased risk of 28-day mortality [HR (95% CI) 1.30 (1.07, 1.58), p = 0.009] and 365-day mortality [HR (95% CI) 1.05 (1.02–1.09), p = 0.005]. Restricted cubic spline curve showed that the relationship between SHR and survival rate was "U-shaped". Conclusions Increase in SHR is associated with an increased risk of 28-day and 365-day all-cause mortality in trauma/surgical ICU patients.